SAFETY AND HEALTH ANALISYS IMPLEMENTATION OF CONSTRUCTION PROJECTS WORK SAFETY IN STUDY ACEH PROVINCY - Yasir Amani (Sisfo: Jurnal Ilmiah Sistem Informasi, 2019)
Material losses suffered by the company due to the applied program and appropriate safety management among other things, cessation of work which resulted in reduced production and increased frequency of repair or rehabilitation equipment/supplies. The purpose of this study was to assess the level of understanding, awareness, and the factors and constraints of the implementation of safety management programs work by the company to the contractor. To achieve this end, it is the goal of research is to identify the level of understanding and awareness of the parties to the contractor (contractor) on safety at construction project sites, identify the factors and constraints of the implementation of safety management program at the project site construction work, and to identify risks to safety that occurred construction project location. The research data obtained through a questionnaire about the respondent's profile and project descriptions, safety program implementation checklists, and questionnaires Perceptions of contractor safety programs. The results show a variable level of understanding and awareness of the parties to the contractor (contractor) on safety at construction project sites, the most dominant subvariabel selected respondents is subvariabel "Provision of First Aid boxes Accident Victim (P3K)" with a mean value of 5.000 and variance 0.000 . In the variable patterns of program implementation and management of safety is commonly done by the company to the contractor (contractor) subvariabel "Restore the Operating System on the Safe state" with 4.4462 mean value and variance 0.407. On the identification of variable risks to safety that occurred at the site of construction projects on the implementation of construction works of sub variables "machine, for example engine powerhouse" with a mean value of 4.7846 with 0.172 variant, "The working environment (outside the building, inside buildings, and under ground) "with a mean value of 4.7846 with 0.172 variant," The cut on the surface", "Burns", and Below members of the body" with a mean value of 4.7846 with variance 0.172, are subvariabel-subvariabel as the most dominant.